2018
DOI: 10.1111/fme.12308
|View full text |Cite
|
Sign up to set email alerts
|

Lambari fish Deuterodon iguape as an alternative to live bait for estuarine recreational fishing

Abstract: Fishing tourism is growing steadily in Brazil. Artisanal fishers meeting the demand for recreational fishing are capturing live juvenile shrimp in the estuaries and selling them for live bait, preventing the recruitment of a larger contingent into the ocean. This study compares the efficiency of using lambari, Deuterodon iguape Eigenmann, as live bait with the shrimp, Penaeus schmitti Burkenroad, while fishing for common snook (Centropomus spp.), as well as to evaluate the swimming behaviour of D. iguape in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
(31 reference statements)
0
17
0
2
Order By: Relevance
“…Salinity addition may influence body behavior, transport stress, fish metabolism, but there is not enough information aiming live baits (Plaut, 2000;Guo, Yan, Ma, Xiao & Zhang, 2013;Souza-Bastos, Bastos, Carneiro & Freire, 2016). Henriques et al (2018) claim some fishers already use lambari species in estuarine sport fishing, however, there are no studies detailing resistance to low salinity concentrations for these species yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salinity addition may influence body behavior, transport stress, fish metabolism, but there is not enough information aiming live baits (Plaut, 2000;Guo, Yan, Ma, Xiao & Zhang, 2013;Souza-Bastos, Bastos, Carneiro & Freire, 2016). Henriques et al (2018) claim some fishers already use lambari species in estuarine sport fishing, however, there are no studies detailing resistance to low salinity concentrations for these species yet.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals were distributed in three different groups (n=10) exposed in salinities of 0 (control), 5 and 10 g L -1 in 20 L glass fish tanks. This experiment was conducted according to Henriques et al (2018). Fish movements were filmed frontally and laterally for 2 minutes at 2 and 45 minutes of exposition.…”
Section: A Bimaculatus Swimming Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…In sport fishing, not only artificial baits are used but also live baits (small shrimps and some other kind of organisms), ideal for bass fishing (Centropomus sp. ), the most wanted fish by recreational fishermen in the southeast region in Brazil and live pray predator species (Barrella et al, 2016;Henriques et al, 2018). Nautical tourism focused on sport fishing creates a vast live bait demand, with marinas serving as intermediates in this trade (Castilho-Barros et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Finding an alternative species to white shrimp, such as some euryhaline fish, for estuarine areas use, is a desire from recreational fishermen, so they would not depend only on one single species with seasonal offer. Henriques et al (2018), thinking on this demand, compared the efficiency of using lambari, Deuterodon iguape Eigenmann 1907, as live bait with the shrimp, Penaeus schmitti Burkenroad, while fishing for common snook (Centropomus sp.). The results showed that there was no significant difference between the live baits used (P. schmitti vs D. iguape).…”
Section: Introductionmentioning
confidence: 99%